Dung beetle diversity and functions suggest no major impacts of cattle grazing in the Brazilian Pantanal wetlands. (27th February 2019) - Correa, César M. A.; Braga, Rodrigo F.; Louzada, Julio; Menéndez, Rosa
Abstract : 1. Dung beetles perform relevant ecological functions in pastures, such as dung removal and parasite control. Livestock farming is the main economic activity in the Brazilian Pantanal. However, the impact of cattle grazing on the Pantanal's native dung beetle community, and functions performed by them, is still unknown. 2. This study evaluated the effects of cattle activity on dung beetle community attributes (richness, abundance, biomass, composition, and functional group) as well as their ecological functions (dung removal and soil bioturbation) in the Pantanal. In January/February 2016, dung beetles were sampled and their ecological functions measured in 16 sites of native grasslands in Aquidauana, Mato Grosso do Sul, Brazil, 10 areas regularly grazed by cattle and six control ungrazed areas (> 20 years of abandonment). 3. In all, 1169 individuals from 30 species of dung beetles were collected. Although abundance, species richness, and biomass did not differ between grasslands with and without cattle activity, species composition and functional groups differed among systems. Large roller beetles were absent from non‐cattle grasslands, and the abundance, richness, and biomass of medium roller beetles was higher in those systems. 4. Despite causing changes in species/functional group composition, the results of this study show that a density compensation of functional groups in cattle‐grazed natural grasslands seems to have conserved the ecological functions (dung removal and soil bioturbation), with no significant differences between systems. 5. Therefore, these results provide evidence that cattle breeding in natural grasslands of the Brazilian Pantanal can integrate livestock production with the conservation of the dung beetle community and its ecological functions. Abstract : This study assessed how cattle grazing impacts dung beetle community and functions in the Brazilian Pantanal. Cattle grazing did not affect the diversity and abundance of dung beetles in the Pantanal, but species composition and functional groups differed among systems. Dung beetle biodiversity and ecological functions are conserved in cattle‐used and non‐cattle natural grasslands.